Recognizing Persian Dramatic Language: A Systemic Approach - Raziyeh Gholipour Hafshejani; Mohammad Dabir Moghaddam (مطالعات زبانی و بلاغی)
Halliday’s systemic functional grammar is one of the most important theories in text analysis and language cognition. Although all literary genres use language, the function of language in dramatic texts is different from the other genres. As drama and dramatic text are indispensable to literature, a more accurate understanding of dramatic language can be achieved by studying the language of dramatic texts within the framework of Halliday’s systemic functional grammar (SFG). The distinguishing features of dramatic language from non-dramatic one can be found by employing Halliday’s quantitative method, notably through interpersonal meta-function. In this study, the authors analyze the mood and tense in five famous contemporary Persian plays within the framework of SFG. We consider the frequency and percentage of the occurrence of mood types and finite forms in each play as a parameter for recognizing dramatic language and comparing it with non-dramatic language. According to the findings of this article, the use of interrogative mood in dramatic texts is more than non-dramatic texts, and the dominant tense in dramatic texts is present tense with a frequency much higher than narrative texts.